(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To identify the species composition of Aspergillus and Penicillium in selected traditional medicine ingredients at three business establishments in urban Hai Phong in 2024. Subjects and Methods: A cross-sectional descriptive study of pure Aspergillus and Penicillium strains selected from colonies grown on DG18 medium isolated from traditional medicinal materials. Thirty samples were randomly selected for identification using PCR and DNA sequencing techniques. Results: The study findings revealed a diverse species composition with a clear predominance of the Aspergillus genus (accounting for 24 out of 30 strains). Aspergillus niger was the most prevalent species (6/30 isolates), followed by Aspergillus chevalieri and Penicillium citrinum (6/30 isolates). Notably, the research successfully characterized highly toxigenic species, including Aspergillus flavus (a potential Aflatoxin producer) and particularly Aspergillus steynii has been reported to produce Ochratoxin A (OTA) at levels up to 1,000 times higher than those of common ochratoxigenic species. Phylogenetic analysis indicated that the fungal strains isolated in Hai Phong exhibited a high degree of genetic consistency, showing 99–100% homology with international reference sequences available on GenBank. Conclusion: The fungal species composition identified in traditional medicine ingredients in urban Hai Phong is not only diverse but also presents a potential risk due to the presence of species capable of producing mycotoxins. Among the 30 fungal strains isolated, 24 belonged to the Aspergillus genus, while 6 were identified as Penicillium. A total of 13 distinct species were successfully characterized, with Aspergillus niger emerging as the most prevalent contaminant.